B-cell and T-cell quantification in minor salivary glands in primary Sjögren's syndrome: development and validation of a pixel-based digital procedure. Issue 1 (December 2016) - Costa, Sebastian; Schutz, Sacha; Cornec, Divi; Uguen, Arnaud; Quintin-Roué, Isabelle; Lesourd, Agnès; Berthelot, Jean-Marie; Hachulla, Eric; Hatron, Pierre-Yves; Goeb, Vincent; Vittecoq, Olivier; Pers, Jacques; et al.
Abstract Background Evaluating lymphocytic infiltration of minor salivary gland biopsy in primary Sjögren's syndrome is challenging. We developed and evaluated a digital method for quantifying B and T lymphocytes in whole minor salivary gland biopsy slides. Methods Minor salivary gland biopsies were immunostained with anti-CD20/anti-CD3 antibodies using red/brown chromogens. Slides were digitised and spliced into mosaics of smaller JPEG format images in which red and brown pixels were counted. ImageJ Cell counter was used for validation. Agreement between the digital and manual methods was evaluated using Bland-Altman plots and the interclass correlation coefficient. External validation relied on the Chisholm-Mason, Tarpley, and focus-score methods. Results Of 62 minor salivary gland biopsy slides, 61.3 % had a Chisholm-Mason grade ≥ III or a focus score ≥1. The number of pixels correlated well with manual cell counts (r = 0.95 for red pixels vs. B cell count and r = 0.91 for brown pixels vs. T cell count). Interclass correlation coefficients between digital and manual counts were excellent (0.92 for B/T cells). B-cell proportion showed a significant positive correlation with the focus score (Spearman's coefficient 0.463, p < 0.0001). Median B-cell proportion was lower in minor salivary gland biopsies with Chisholm grades I–II (2.5 % (0.2–13.9)) than III–IV (30.0 % (15.5–45.2)) and increased with Tarpley's class (1, 2.2 % (0.2–6.6); 2, 27.2 % (13.0–38.9); and 3–4, 48.5 % (29.4–56.4);p < 0.001 for all comparisons). Minor salivary gland biopsy B-cell proportion was also significantly correlated with several markers of clinical and biological activity of the disease, especially with markers of systemic B-cell hyperactivation. Conclusion The digital procedure proved accurate compared to the reference standard, producing reliable results for whole tissue sections. Trial registration ClinicalTrials.gov [NCT00740948 ]. Registered 22 August 2008.